Aplikasi Kontrol Lampu Rumah Berbasis Smartphone Android untuk Mendukung Smarthome - Erfanti Fatkhiyah; Muntaha Nega; Uning Lestari (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2018)
Along with the rapid development of technology that runs dynamically, then this has a lot to give a significant effect on the field of property. Utilization of electrical energy is currently less effective because many household electronic appliances that use electrical energy and its use is very excessive. Excessive use of electrical energy will cause electrical energy to be scarce. Technological developments such as smart phones that have many innovations to overcome the problem of use or electricity savings. Electrical switches can be replaced by using a relay and controlled via a microcontroller connected to a pre-programmed smart phone. With the existence of Ethernet shield equipment that can communicate with the microcontroller through serial communication with the command communication on / off switch via a smart phone with wireless connection to the Ethernet shield equipment is a solution to overcome the switch electrical switch, android-based smart phone that has been programmed lamp control can turn off or turn on home lights with distance to the range of available wifi connections.